Valoración del paisaje natural de la parroquia Canchagua del cantón Saquisilí en la provincia de Cotopaxi, propuesta de conservación de las unidades del paisaje, 2022. - Nacevilla Herrera, Wilmer Daniel (2022)
The present research project was developed with the purpose of evaluating the quality of the existing natural landscape in the Canchagua Parish, located in the Saquisili canton, Cotopaxi Province, for which the analysis of the conditions of the natural landscape was established, and a methodology was proposed that focuses on the determination of the landscape units, production systems and quality of visual absorption (CAV) for which different methodologies were applied, Among these, the methodology applied was based on the guidelines established by the Bureau of Land Management (BLM) method, which allowed establishing qualitative and quantitative values established in numerical weighting scales focused on the determination of the components (texture, color, relief, erodibility, slope, vegetation, scenic context, line, spatial configuration) that form the landscape units based on subjective evaluations presented by the researcher through the analysis of photographs of the study area; For this purpose, field visits and surveys were carried out based on non-probabilistic random sampling in order to learn directly about the different activities that take place in the area. The results show that the area has a high visual quality and a moderate quality of visual absorption, which requires management activities and conservation of the natural landscape. Based on these results, conservation, regeneration and maintenance activities were proposed for the study area.